Whole genome sequencing revealed esophageal squamous cell carcinoma related biomarkers - Mingjun Li; Lei Li; Xizi Wang; Yanwei Zhao; Peina Du; Wei Wang; Zhenxing Wang; Yadong Wang; Yanxing Sheng; Mingliang Gu; Xiaodong Jia (PLoS ONE, 2025)
Esophageal squamous cell carcinoma (ESCC) is among the most frequently diagnosed cancer types, and affected patients frequently experience poor prognostic outcomes and high mortality rates. Many genomic studies of ESCC have been performed in recent years, yet the mutational mechanisms driving ESCC and their clinical implications remain incompletely understood. In this study, paired tumor and normal tissue samples from 22 patients with ESCC were used for whole genome sequencing-based analyses of genome-wide mutational events. These comprehensive analyses enabled the detection and characterization of various mutation subtypes in ESCC including somatic single-nucleotide variants, small insertions and deletions, copy number variations, structural variations, and circular extrachromosomal DNA. Of identified genes harboring non-silent mutations, TP53, NOTCH1, CSMD3, EP300, and FAM135B were the most frequently mutated genes in this study and they were annotated in the COSMIC Cancer Gene Census. With the exception of aging-related signatures, an APOBEC-associated mutational signature was the dominant mutational feature detected in ESCC samples, suggesting that APOBEC-mediated cytidine deamination is likely a major driver of mutations in this cancer type. Notably, our study also detected circular extrachromosomal DNA (ecDNA) events in these ESCC patient samples. The oncogenes COX6C, PVT1, and MMP12 as well as the oncogenic long non-coding RNA AZIN1-AS1 which were detected in ecDNA regions in these analyses may be associated with worse disease-free survival in ESCC patients.